Development of HOTS Test in Microbiology Course using Microsoft Office and Visual Basic for Application - ANNUR INDRA KUSUMADANI; RIO TAUFIQ NUGROHO; ATIKA INTAN PRATIWI (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2016)
This research aims to develop higher-level thinking tests on microbiology using computer assisted to measure high-level thinking skills of students who attended the Microbiology Course. The instrument was developed on Microsoft Office Power Point and Visual Basic for Application. The research stages followed the ten steps of Borg and Gall's R and D, done from February to July 2016. To test the validity of the instruments, the following steps were done: (1) expert validation involving microbiologists, ICT specialists, expert in research and evaluation of education; (2) small trial involved 12 students who took micobiology at Department of Biology Education of Universitas Muhammadiyah Surakarta (UMS); (3) Test involves 20 students who took the same courses; and (4) external validity test involving 20 students who took the same courses. Pearson correlation analysis was applied for analysis the external validity test. The findings were the instruments were valid, reliable with high coefficient of 0.872> 0.456 (r table), level of difficulty with difficulty index of 0.3 to 0.7, and discriminant power either with index of 0.3 to 0.7. External validity was 0.757 (Strong). Conclusion of the study is a test instrument is feasible and effective to measure high-level thinking skills of students in microbiological related content.